Evaluasi Jaringan Jalan Hutan Di Areal PT INhutani II, Pulau Laut, Kalimantan Selatan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRACT Forest road network plays a very important role in opening up a forest area, especially in a tropical rain forest where the acessibility is not good. Raster method shows that topography conditions in southern part of Pulau Laut are mostly flat (95%). It is possible to build straight roads with large curve. Road network in concession area (HPH) and in plantation area (1-111), which are showed by road density, road spacing, mean skidding distance and percentage of opening up are different. In the concession area road density, road spacing, mean skidding distance and percentage of opening up are 11.1 mita, 903.8 m, 280.4 m and 80.6% respectively. The value of the road net adjustments is 1.16, In the plantation area road density, road spacing, mean skidding distance and percentage of opening up are 26.0 m/ha, 384.6 m, 137.8 m and 69.9% repectively with the road net adjustments of 1.43. In general it can be concluded that road network in the forest concession and plantation area is satisfactorily good in term of quality and intensity